PENERAPAN MODEL TEAM GAME TOURNAMENT DALAM PENINGKATAN KETERAMPILAN PENJUMLAHAN PECAHAN PADA SISWA KELAS V SD - Masitoh, Dewi (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract: The purpose of this research are: 1) to describe the application of Team Game Tournament model which can be improve the fractions addition skill for the fifth grade students in SDN Bumirejo 4; 2) to describe the constraint and the solution of the application of Team Game Tournament model in fractions addition skill improvement for the fifth grade students in SDN Bumirejo 4. The writer employs Classroom Action Research method collaborative. even if the researcher becomes the observer towards the action research process. The method is divided into 3 cycles, each cycle consist of planning, action, observation, and reflection. The data sources are teacher, students, researcher, colleague, and documents. The techniques of data collection are observation, field notes, test, and documentation. The data validity uses triangulation source and data analysis techniques are statistic descriptive qualitative and quantitative. The results showed that the Team Game Tournament model can be improve skill fraction editon. Keywords: TGT model, skill improvement, fractions addition Abstrak: Tujuan penelitian ini adalah: 1) mendeskripsikan penerapan model Team Game Tournament yang dapat meningkatkan keterampilan penjumlahan pecahan pada siswa kelas V SD 4 Bumirejo; 2) mendeskripsikan kendala dan solusi penerapan model Team Game Tournament dalam peningkatan keterampilan penjumlahan pecahan pada siswa kelas V SD. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif yang dilaksanakan dalam 3 siklus dengan setiap siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Teknik pengumpulan datanya adalah observasi, catatan lapangan, tes dan dokumentasi. Validitas data menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa model Team Game Tournament dapat meningkatkan keterampilan penjumlahan pecahan pada siswa kelas V SD. Kata kunci: model TGT, peningkatan keterampilan, penjumlahan pecahan